Social Economics and Evolutionary Institutionalism Today: Theoretical Components and "Heterodox" Convergence in a Socio-Economic Perspective. Issue 1 (2nd January 2017) - Elsner, Wolfram
Abstract : This paper discusses theoretical and methodological elements that constitute social economics. It also considers those elements for evolutionary (Veblenian) institutional economics. It investigates how these "heterodoxies" may further converge . Such convergence would probably not trigger a complete unification, but lead to a broadly defined common research program and a strategy for joint "heterodox" survival, in face of the ranking game of the neoclassical "mainstream" and of the dominant powers supporting it as the discipline providing ideological legitimization. A common denominator of "heterodoxies" in terms of real-world orientation, direct interdependency and interaction of agents (social decision situations), appropriate complexity, and the treatment of values is drafted. Theoretical concepts discussed include complex and open systems, individual agency, institutions, embeddedness, networks, social reform, and process orientation. Formal methodological developments considered are complex modeling, game theory, or computer simulations. We arrive at a more formal common basis, which we term socio-economics. We also consider the relations of evolution and institutions, the institutional dichotomy, and the theory of institutional change. The monism of the "market" of the "mainstream" turns out to dissolve into the institutional diversity of real-world network forms, which helps explaining real-world forms of markets, hierarchies, or spatial clusters. Focuses of "heterodox" convergence will have to be the related " microfoundations " and "macrofoundations" projects, integrating an interdisciplinary "naturalistic" approach to genetic-cultural co-evolution of cooperation, and social reform . While modern socio-economics makes "heterodoxies" leading in economic research, their future still appears open between ideological cleansing and extinction through the mainstream, and proactive paradigmatic pluralism.